Biochemical, histopathological and morphological profiling of a rat model of early immune stimulation: relation to psychopathology - Kubesova, Anna; Tejkalova, Hana; Syslova, Kamila; Kacer, Petr; Vondrousova, Jana; Tyls, Filip; Fujakova, Michaela; Palenicek, Tomas; Horacek, Jiri (PloS one, 2015)
Perinatal immune challenge leads to neurodevelopmental dysfunction, permanent immune dysregulation and abnormal behaviour, which have been shown to have translational validity to findings in human neuropsychiatric disorders (e.g. schizophrenia, mood and anxiety disorders, autism, Parkinson's disease and Alzheimer's disease). The aim of this animal study was to elucidate the influence of early immune stimulation triggered by systemic postnatal lipopolysaccharide administration on biochemical, histopathological and morphological measures, which may be relevant to the neurobiology of human psychopathology. In the present study of adult male Wistar rats we examined the brain and plasma levels of monoamines (dopamine, serotonin), their metabolites, the levels of the main excitatory and inhibitory neurotransmitters glutamate and γ-aminobutyric acid and the levels of tryptophan and its metabolites from the kynurenine catabolic pathway. Further, we focused on histopathological and morphological markers related to pathogenesis of brain diseases--glial cell activation, neurodegeneration, hippocampal volume reduction and dopaminergic synthesis in the substantia nigra. Our results show that early immune stimulation in adult animals alters the levels of neurotransmitters and their metabolites, activates the kynurenine pathway of tryptophan metabolism and leads to astrogliosis, hippocampal volume reduction and a decrease of tyrosine hydroxylase immunoreactivity in the substantia nigra. These findings support the crucial pathophysiological role of early immune stimulation in the above mentioned neuropsychiatric disorders.
Keywords: Psychopathology; kynurenin; astrocyty; Biogenic Monoamines; Neuroimmunomodulation; metabolické sítě a dráhy; metabolom; krysa rodu Rattus; tryptofan; psychopatologie; Kynurenine; Microglia; Neurotransmitter Agents; Metabolome; Disease Models, Animal; duševní poruchy; Astrocytes; Metabolic Networks and Pathways; neuroimunomodulace; mužské pohlaví; zvířata; Rats; Animals; Male; mozek; Brain; tělesná hmotnost; biogenní monoaminy; modely nemocí na zvířatech; neurotransmiterové látky; Mental Disorders; mikroglie; Body Weight; Tryptophan